NEUROPROTECTIVE EFFECT OF EPALRESTAT ON MEMORY IMPAIRMENT IN STREPTOZOTOCIN-INDUCED TYPE-2 DIABETIC RATS USING DIFFERENT BEHAVIORAL MODELS. - Jaiswal, Shruti; Ss, Torgal; Mishra, Sanjay (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study was designed to evaluate the protective effects of epalrestat (EPS) on memory and learning in type-2 diabetes. Methods: Sixty percent high-fat diet for 2 weeks and a single dose of streptozotocin (35 mg/kg, ip) was used to induce memory impairment in rats. Once the diabetes is confirmed, test drug (EPS - 13.5, 27, and 54 mg/kg, oral) and donepezil (1 mg/kg, oral) were administered to different groups of rats for 4 weeks followed by an assessment of memory and learning deficit using behavioral paradigms: Elevated plus maze (EPM), Morris water maze (MWM), and passive avoidance test. Results: EPS and donepezil showed significant improvement in learning and memory of rats, as indicated by markedly decreased escape latency to reach a hidden platform and increased time spent in target quadrant using MWM task, reduced transfer latency in EPM, and also there is a significant increase in the transfer latencies using passive avoidance test were noted. Memory-enhancing activity of EPS (13.5, 27, and 54 mg/kg) was comparable with the diabetic control group. Conclusion: The study findings suggest that memory-enhancing effect of EPS may be mediated by its antioxidant and anti-inflammatory activities. This recommends the potential effect of EPS therapy as a useful memory restorative agent in the treatment of neurodegenerative disease seen in type-2 diabetes rat.